The interaction of a wing-tip vortex and free-stream turbulence - Bailey, Sean C. C (University of Ottawa (Canada), 2007)
The formation and development of a vortex generated by a wing with a NACA0012 airfoil section in the presence of grid-generated turbulence was studied at Reynolds numbers 29000 in a water tunnel and 240000 in a wind tunnel. Flow visualization indicated that the free-stream turbulence did not significantly affect the large-scale features of the vortex during its formation, however, it resulted in an increase in the turbulence within the vortex as well as an increase in the wandering motion of the vortex. Extensive single-point and two-point, three-component hot-wire anemometry.measurements were conducted for the no-grid case and four cases using two different grids. Time-averaged statistics were found to be significantly influenced by wandering of the vortex position. Quantitative analysis of vortex wandering showed a significant increase in its amplitude with increasing free-stream turbulence. The radial profile of the circumferential velocity with respect to the wandering vortex axis was reconstructed using two-point measurements. The rate of decay of the peak circumferential velocity was found to increase with increasing free-stream turbulence, but the radial location at which it occurred did not change significantly. Analysis of the velocity signals indicated that the turbulent eddies from the wing's wake and the grid turbulence tend to wrap around the vortex core.
Keywords: Engineering, Aerospace.